2019
DOI: 10.1002/jsfa.9496
|View full text |Cite
|
Sign up to set email alerts
|

Rootstock effects on grape anthocyanins, skin and seed proanthocyanidins and wine color and phenolic compounds from Vitis vinifera L. Merlot grapevines

Abstract: BACKGROUND Rootstocks affect vegetative and reproductive parameters of the scion. However, limited knowledge exists on the effects of the adoption of a specific rootstock on grape and wine phenolic composition, which contribute to certain sensory attributes such as color, body and astringency of wine. These compounds are mainly affected by the variety, viticultural management and rootstock. The aim of this work was to study the influence of eight rootstocks on grape anthocyanin content, skin and seed proanthoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 34 publications
2
24
0
Order By: Relevance
“…Contrarily, a recent study showed that ‘Merlot’ grafted onto SO4, 101-14, and 110R presented higher concentrations of proanthocyanidins in skins in one growing season. The differences in the rootstock effects on flavan-3-ols may be affected by scion cultivars and climatic differences, and further studies are necessary to understand this [31]. Notably, in this study, Ganzin 1 slightly reduced almost all the individual flavan-3-ol concentrations, indicating that Ganzin 1 tended to inhibit the accumulation of flavan-3-ols in grape skins.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Contrarily, a recent study showed that ‘Merlot’ grafted onto SO4, 101-14, and 110R presented higher concentrations of proanthocyanidins in skins in one growing season. The differences in the rootstock effects on flavan-3-ols may be affected by scion cultivars and climatic differences, and further studies are necessary to understand this [31]. Notably, in this study, Ganzin 1 slightly reduced almost all the individual flavan-3-ol concentrations, indicating that Ganzin 1 tended to inhibit the accumulation of flavan-3-ols in grape skins.…”
Section: Resultsmentioning
confidence: 70%
“…In 2015, except for SO4, all the rootstocks showed slight positive effects on anthocyanin accumulation. Notably, ‘Merlot’ and ‘Shiraz’ grafted onto 110R both possessed higher concentrations of anthocyanins than ungrafted grapevines in the previous studies [31,32]. However, in 2016, anthocyanin concentrations were slightly reduced by rootstocks, except 5BB and 110R, which exhibited a negligible influence.…”
Section: Resultsmentioning
confidence: 74%
“…'IAC 572' and 'IAC 766' are considered vigorous rootstocks. Gutiérrez-Gamboa et al (2018) emphasizes that vigorous rootstocks give rise to a long vegetative cycle to the graft, delaying ripening. Results of this study suggest a faster ripening related to higher degradation of organic acids and higher accumulation of soluble solids in berries harvested from plants grafted on 'IAC 572'.…”
Section: Fruit Qualitymentioning
confidence: 99%
“…These differences indicate that grape growing practices have a significant influence on wine phenolic composition, as suggested by Gutiérrez-Gamboa et al (2019). Other factors that can affect this parameter include climatic and processing conditions.…”
Section: Phenolic Composition and Antioxidant Activitymentioning
confidence: 91%